A Proposal of Digital Contents Copyright Protection by using Blockmarking Technique - Thanh, Ta Minh; Le Danh Tai (Computer Science, 2025)
Recently, blockmarking technique blockmarking is proposed for a new hybrid model based on the combination of blockchain and watermarking method. In this model, it not only achieves the goal of image copyright protection but also stores the image into the blockchain network such as IPFS system. In this paper, we propose a new DRM system by inheriting the idea of blockmarking. The copyright contents can be distributed via IPFS blockchain, then be restored by using the reconstruction license for each legal user. Also, in our method, based on the reconstruction licenses, the distributed contents can be reconstructed from IPFS with various watermarking patterns. It helps us can manage the legal users and trace the traitor if a dispute occurs. The experimental results show that our method successfully achieved the purpose of digital copyright protection.